Nurra Chatbot For Islamic Education Among Generation Z - Raisyal Dimas Prayoga; Rizki Hikmawan; Muhammad Ariestama Putra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study develops and validates the NURRA Islamic AI Assistant as a digital learning tool designed to support Islamic education for Generation Z. The research responds to the increasing reliance of students on digital platforms for religious learning and the associated risks of misinformation in unguided environments. A development and validation approach was employed using a Design and Development Research model combined with an agile iterative cycle. The prototype integrates curated Islamic sources, including Waqfeya and Maktabah Syamilah, and applies content filtering and ethical safeguards to maintain theological accuracy and responsible communication. Six experts in Islamic education, educational technology, ethics, linguistics, media learning, and computer science evaluated the system using a five-point Likert scale instrument. Data were analysed descriptively and showed that the prototype achieved a very valid classification across content accuracy, ethical compliance, usability, and practical functionality. System testing further demonstrated that the chatbot is capable of generating relevant responses, supporting learners with diverse types of questions, and providing transparent fallback responses when source-based retrieval is unavailable. The findings indicate that NURRA can function as a complementary learning tool that strengthens access to authentic Islamic knowledge and aligns with the digital characteristics of Generation Z learners. The validated model highlights the feasibility of integrating AI into Islamic education in a responsible manner and offers a foundation for classroom implementation, future system refinement, and broader user trials.